2017
DOI: 10.24329/aspikom.v1i1.9
|View full text |Cite
|
Sign up to set email alerts
|

Budaya Populer Jepang di Indonesia : Catatan Studi Fenomenologis Tentang Konsep Diri Anggota Cosplay Party Bandung

Abstract: The research is about self concept in the relations with popular culture, that PengantarRagam budaya populer Jepang yang kini 'populer' di Indonesia meliputi banyak bentuk mulai dari Film, Musik, anime, manga/komik, hingga fashion atau lebih tepatnya gaya pakaian kaum muda Jepang. Cacatan studi fenomenologis yang disajikan dalam makalah ini tidak dimaksudkan untuk menyoroti seluruh bentuk budaya populer Jepang di atas. fokus tulisan ini lebih pada fenomena gaya pakaian kaum muda Jepang atau lebih populer d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 1 publication
(3 reference statements)
0
6
0
4
Order By: Relevance
“…From this definition it can be concluded that culture is all things that are the work of human creation as the subject of society. Included in this case is the language which is the result of human creation, used by humans, and passed down from generation to generation [8]. Culture is synonymous with the ways of a human group (the ways of a people).…”
Section: Culturementioning
confidence: 99%
“…From this definition it can be concluded that culture is all things that are the work of human creation as the subject of society. Included in this case is the language which is the result of human creation, used by humans, and passed down from generation to generation [8]. Culture is synonymous with the ways of a human group (the ways of a people).…”
Section: Culturementioning
confidence: 99%
“…Beragam budaya Jepang seperti film, musik, anime, manga hingga fashion sangat populer di Indonesia (Venus & Helmi, 2010). Banyak pemelajar yang memulai pelajaran bahasa Jepang karena tertarik dengan hal tersebut.…”
Section: Kajian Pustakaunclassified
“…They generally do not perform individual behavior but group behavior namely members of the cosplay community. Because of their unique clothing styles so that they often become the center of attention as well as the center of questions from the community (Venus and Helmi 2010). Cosplay activities are still considered as clowns in the community and their own friends.…”
Section: Introductionmentioning
confidence: 99%